Balance Scorecard sebagai Rerangka Pengukuran Kinerja Perusahaan secara Komprehensif dalam Lingkungan Bisnis Global - Lasdi, Lodovicus (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2002)
The leading indicators of business performance cannot be found in financial data alone. Quality, customer satisfaction, innovation, market share-metrics like these often reflect a company's economic condition and growth prospects better than its reported earnings do. Executives want a balanced presentation of measures that allow them to view the company from several perspectives simultaneously . Balanced scorecard as a new performance measurement system gives lop managers a fast but comprehensive view of their business. The balanced scorecard includes financial measures that tell the results of actions already taken; and it complements those financial measure with three sets of operational measures having to do with customers satisfaction, internal processes and the organization's ability to learn and improve the activities that drive future financial performance.